Implications of an epidemiological study showing an association between in utero NDMA exposure and childhood cancer. (2nd June 2021) - Engelward, Bevin P.
Abstract: Exposure to N ‐nitrosodimethylamine (NDMA) has recently been linked to a childhood cancer cluster in Wilmington, MA, which is home to the Olin Chemical Superfund Site. When it was discovered in the 1990's that 22 children in a town of under 22, 000 people got cancer, the community took action and pressed for an investigation into the possibility that chemicals from the Olin Chemical site had contaminated their water. This led to the eventual discovery that NDMA was present in the town water supply. NDMA has long been known for its potent carcinogenicity in animal models, and so the community pointed to NDMA as a possible cause. This led to an investigation by the Massachusetts Department of Public Health, which, in 2021, released its findings showing an association between NDMA exposure in utero and childhood cancer. The mission of the NIEHS Superfund Research Program is to protect human health from hazardous substances. In 2017, in response to community concerns, a team at MIT created the MIT Superfund Research Program Center with a focus on research related to NDMA. Just 1 week prior to the release of the Department of Public Health study, the MIT Superfund Research Program Center published a manuscript in Cell Reports that identifies the Alkyladenine DNA glycosylase (AAG) as a possible genetic susceptibility factor. This commentary provides an author's perspective on the context and implications of this and related research.